Compliance of EIA Approval Conditions for Kuala Lumpur - Putrajaya - KLIA Highway Project - Aweng Eh Rak; Zainai Mohamed (2011)
The study was to identify the compliance of Environmental Impact Assessment (EIA) Approval Conditions in conditions terms of total suspended solods (TSS) discharge from the silt trap and in the rivers for Kuala Lumpur - Putrajaya - KLIA highway construction project, Malaysia. The data from August 2005 to May 2007 was obtained from Department of Environment, Kuala Lumpur. This project was chosen for the study because this project was among the early projects after the implementation of Erosion and Sediment Control Plan (ESCP). The highway cut across several rivers where a total of suspended solids (TSS) were measured at upstreams and downstreams with a total of twelve (12) stations. In addition, twelve (12) sampling stations for the silt trap discharge located along the rivers were also measured. The results have shown that fifteen (15) out of one hundred and thirty two (132) samplings for river stations recorded incompliance of about 11.4% and seven (7) out of fifty two (52) samplings for silt trap discharge stations recorded incompliance of about 13.5%.